2017
DOI: 10.1371/journal.pone.0179204
|View full text |Cite
|
Sign up to set email alerts
|

α-Mangostin ameliorates hepatic steatosis and insulin resistance by inhibition C-C chemokine receptor 2

Abstract: Obesity induces various metabolic diseases such as dyslipidemia, nonalcoholic fatty liver disease (NAFLD), and type 2 diabetes. Fat expansion in adipose tissue induces adipose tissue dysfunction and inflammation, insulin resistance, and other metabolic syndromes. α-Mangostin (α-MG) has been previously studied for its anti-cancer, anti-inflammatory, and antioxidant activities. In this study, we investigated the effects of α-MG on adipose tissue inflammation and hepatic steatosis. We categorized study animals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 31 publications
7
20
0
2
Order By: Relevance
“…Consistent with the increased expression of serum inflammatory cytokines (such as MCP-1, TNF-α and IL-6) in obese mice, we demonstrated that the expression of CCR2 and macrophage infiltration in SAT and VAT were significantly increased in diet-induced obese mice. This was also observed in other studies of WAT in diet-induced obese rodent models ( Kim et al, 2017 ; Weisberg et al, 2006 ). In vitro, RES inhibited the mRNA and protein expression in CCR2 of THP-1 monocytes ( Cullen et al, 2007 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with the increased expression of serum inflammatory cytokines (such as MCP-1, TNF-α and IL-6) in obese mice, we demonstrated that the expression of CCR2 and macrophage infiltration in SAT and VAT were significantly increased in diet-induced obese mice. This was also observed in other studies of WAT in diet-induced obese rodent models ( Kim et al, 2017 ; Weisberg et al, 2006 ). In vitro, RES inhibited the mRNA and protein expression in CCR2 of THP-1 monocytes ( Cullen et al, 2007 ).…”
Section: Discussionsupporting
confidence: 86%
“…Internal adipose tissue makes up approximately 20% of the total body fat mass and mainly consists of visceral adipose tissue (VAT). In obesity, inflammation can occur due to increased levels of chemokines (such as CCL2 and CXCL1) and inflammatory cytokines (such as tumor necrosis factor α (TNF-α) and interleukin-6 (IL-6)) secreted from accumulated fat in hepatocytes and adipocytes, causing insulin resistance ( Kim et al, 2017 ; Xu et al, 2003 ). In obesity, macrophage infiltration in adipose tissue was observed in both rodents and humans ( Fjeldborg et al, 2014 ; Harford et al, 2011 ; Michaud et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, α-MG decreased hepatic steatosis through the hepatic SirT1-AMPK and PPAPγ pathways in obese mice [38]. In addition, it is reported that α-MG ameliorated adipose inflammation and hepatic steatosis in obese C57BL/6 mice receiving a high-fat diet [60], corroborating our findings in this study.…”
Section: Discussionsupporting
confidence: 90%
“…As the most important secondary metabolite in the plant, α-MG demonstrates a wide variety of pharmacological effects including anti-inflammation [ 14 , 15 ], anti-oxidant [ 16 ], anti-apoptosis, antibacterial [ 17 ], and anti-Alzheimer’s disease [ 18 ]. α-MG was reported to significantly ameliorate hepatic steatosis in vivo [ 19 , 20 ]. In addition, α-MG was shown to reduce the risk of liver fibrosis on thioacetamide-induced cirrhosis in rats [ 21 ].…”
Section: Introductionmentioning
confidence: 99%